(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women constituting half of our population speak to an undiscovered wellspring of economic development and entrepreneurship is one method for utilizing that tremendous pool of human resource as arbiters of that development. In spite of the fact that India has seen a noteworthy ascent in the quantity of women entrepreneurs in the course of recent decades impacting the statistic qualities of business yet the entrepreneurial world in the nation is as yet ruled by men. There is abundant confirmation to propose that other than social limitations, the entrance to formal wellsprings of credit is one of the main considerations smothering the development of women entrepreneurship in India. While banks don’t purposely bar women, something in the system isn’t working. In rustic territories as well as even in enormous urban areas there are women with entrepreneurial soul who can’t understand their maximum capacity without banking offices. It thusly ends up basic that any vision of India’s financial system in the coming years takes this financial hole as an issue of concern.